Combined lack of blood pressure and lipid control is a major risk factor for mortality in hypertensive patients: a single-center study. (25th November 2020) - Magkas, N; Georgiopoulos, G; Konstantinidis, D; Manta, E; Kouremeti, M; Dilaveris, P; Chrysochoou, C; Tzorovili, E; Antoniou, C; Tsiamis, E; Tousoulis, D; Tsioufis, C
Abstract: Background: Hypertension and dyslipidemia are well-known risk factors for cardiovascular disease (CVD). In such patients, lowering blood pressure (BP) and low-density lipoprotein cholesterol (LDL-C) and targeting to values below pre-specified cut-offs prevents CV events and improves prognosis. However, the impact of both BP and LDL-C control as compared to control of only one and/or none of these two risk factors is not well-studied. Methods: Among 2, 380 treated patients with hypertension and no overt CVD at baseline, we assessed the trajectory of BP control in 1, 142 subjects with 4 or more follow up visits; BP control was defined as BP<140/90 mmHg in half or more visits. In the same subgroup, data on lipid control according to LDL-C goals were available in 1, 032 patients in 2 or 3 visits. The HeartScore was used to estimate the risk of all-cause death at baseline. Results: Across a median follow up of 108 months, 26 deaths (2.44%) were recorded. Despite appropriate anti-hypertensive treatment, 376 patients (32.92%) did not achieve conventional BP control in half or more of follow-up visits. Respectively, 59.83% of the study population did not meet the LDL-C goals in at least one assessment. Patients with suboptimal BP control had almost 3-fold increased risk for all-cause mortality (HR=2.85, 95% CI 1.31–6.21, P=0.008) as compared to subjects with effective control. This association was not attenuated after taking into account age, gender, body mass index, smoking, and diabetes mellitus (adjusted HR=2.54, 95% CI 1.13–5.72, P=0.025). Ineffective LDL-C control was not related to death (HR=1.31, 95% CI 0.688–2.48). However, patients who did not reach treatment goals for both BP and LDL showed substantially increased risk for all-cause mortality (HR=5.42, 95% CI 1.09–26.9, P=0.039). Importantly, suboptimal BP control in our cohort of hypertensive patients was associated with death independently of the HeartScore (adjusted HR=2.65, 95% CI 1.22–5.77, P=0.014) and conferred incremental reclassification value on top of the baseline risk (continuous NRI=0.467, P=0.016). Conclusions: Suboptimal BP control was related to all-cause mortality in our cohort of hypertensive patients; importantly, this association was substantially stronger in concurrent presence of LDL-C values above treatment targets, thus, highlighting the need for combined achievement of BP and LDL-C control. Moreover, association of suboptimal BP controlwith death was independent of the HeartScore, suggesting that BP control should be considered in risk stratification of hypertensive patients Funding Acknowledgement: Type of funding source: None